Lanskap linguistik di stasiun Surabaya Pasarturi - Anita Nur Aini; Yarno Yarno; R. Panji Hermoyo (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
The use of language can be seen in the private and public domains. The purpose of this study is to describe the use of language in signs in the linguistic landscape at Surabaya Pasarturi Station and to answer questions about the actors and functions of the linguistic landscape at Surabaya Pasarturi Station. This research method uses descriptive qualitative. Methods of data collection is done by observation and photography techniques. The data in this study are visual data, namely the results of visual image portraits containing language signs at Surabaya Pasarturi Station. The results of the study show that there are six language variations in the linguistic landscape at Surabaya Pasrturi Station, monolingual, bilingual, and multilingual. The language variations consist of monolingual languages, namely Indonesian, English and Javanese. Two variations of bilingual language were found, namely Indonesian-English and Indonesian-Javanese, while multilingual language variations found one data, namely those showing Indonesian-English-Javanese. Actors of linguistic landscape signs in Surabaya Pasarturi Station are from public authorities and private/commercial actors. There are several functions used at Surabaya Pasarturi Station, namely as building markers, tools and rooms; as an information guide; as prohibitions and warnings; as advertisement distribution.